Economic study on production and marketing of shrimp and prawn seed in Bangladesh (Journal of the Bangladesh Agricultural University, 2012)
Shrimp farming and related activities contribute significantly to the national economy of Bangladesh. Successful shrimp culture depends mainly on the availability of healthy and quality shrimp seeds. The present study was designed to analyze the production and marketing system of shrimp seed in Bangladesh. A total sample of 80 stakeholders comprising each of 20 operators of bagda and golda hatcheries, and each of 20 shrimp seed traders and faria (bapari) were selected purposively. Data and information mainly on shrimp seed production and marketing were collected for 2009-2010 from Coxs Bazar and Jessore districts depending upon the concentration of hatcheries established for shrimp seed production. In most cases tabular method of analysis and flow diagram were used. The average sizes of bagda and golda hatcheries were 2.6 and 2.9 acres and the corresponding productions were 430 and 250 million PL per year in Coxs Bazar and Jessore districts respectively. Per hatchery per year total costs, gross returns and net returns were Tk 50.2 and 19.6 million; Tk 90 and 56.3 million; and Tk 39.6 and 36.7 million in Coxs Bazar, and Jessore districts respectively. Shrimp seed production is capital intensive and it is risky business. Although shrimp seed production cost is very high but the farm could earn higher profit by ensuring better culture and management. Marketing channel and distribution system of shrimp seed were identified in the present study. Shrimp seed passed from hatcheries to shrimp farmers followed by sequence of intermediaries. Hatcheries directly sell about 80% shrimp seed to aratdar and rest 20% to shrimp seed traders but in case of shifting shrimp seed by cargo plane almost all are sold to aratdar in sale centre. The aratdar is a commission agent who has a fixed establishment and helps the traders (beparies) to sell their products and usually charges a fixed commission of Tk 25-30 per 1000 PL sales revenue. However, less number of intermediaries was involved in shrimp seed marketing.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11037   J. Bangladesh Agril. Univ. 9(2): 247256, 2011